Ascertaining the relationship between Salmonella Typhimurium and Salmonella 4,[5],12:i:- by MLVA and inferring the sources of human salmonellosis due to the two serovars in Italy - Barco, Lisa; Barrucci, Federica; Cortini, Enzo; Ramon, Elena; Olsen, John E.; Luzzi, Ida; Lettini, Antonia A.; Ricci, Antonia (Frontiers in Microbiology, 2015)
The current picture of human salmonellosis shows S. Typhimurium and S. 4,[5],12:i:- as the most common serovars in Italy. The aims of this study were to investigate the genetic relationship between these serovars, as well as to test the possibility of inferring sources of human salmonellosis due to S. Typhimurium and S. 4,[5],12:i:- by using MLVA subtyping data. Single isolates from 268 human sporadic cases and 325 veterinary isolates (from pig, cattle, chicken and turkey) collected over the period 2009-2011 were typed by MLVA, and the similarities of MLVA profiles were investigated using different analytical approaches. Results showed that isolates of S. 4,[5],12:i:- were more clonal compared to S. Typhimurium and that clones of both serovars from different non-human sources were very close to those which were responsible for human infections, suggesting that source attribution by MLVA typing should be possible. However, using the Asymmetric Island Model it was not possible to obtain a confident ranking of sources responsible for human infections based on MLVA profiles. The source assignments provided by the model could have been jeopardized by the high heterogeneity found within each source and the negligible divergence between sources as well as by the limited source data available, especially for some species.